2006
DOI: 10.1038/sj.bjc.6603250
|View full text |Cite|
|
Sign up to set email alerts
|

Use of nonsteroidal anti-inflammatory drugs and risk of oral cancer: a cohort study

Abstract: Epidemiologic data regarding the chemopreventive potential of nonsteroidal anti-inflammatory drugs (NSAIDs) against oral cancer are sparse. We found a relative risk for oral cancer of 1.2 (95% CI, 1.0 -1.6) among 169 589 Danish NSAID users (X2 prescriptions), with no apparent trends in subgroups. Our study provided no clear evidence that NSAIDs may protect against oral cancer. There is substantial experimental and epidemiological evidence that aspirin and other nonsteroidal anti-inflammatory drugs (NSAIDs) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 12 publications
(14 reference statements)
0
40
0
Order By: Relevance
“…Six papers met all criteria (one after communication with the author to obtain 95% CI). Papers by Sørensen et al [21] and Friis et al [22] showed similar study populations, methodologies, exposure variables, and apparent overlap of outcome measures. Only the Friis et al's [22] study was included as it provided a better measurement of risk, stating standardized rate ratios (SRR).…”
Section: Included Studiesmentioning
confidence: 76%
See 2 more Smart Citations
“…Six papers met all criteria (one after communication with the author to obtain 95% CI). Papers by Sørensen et al [21] and Friis et al [22] showed similar study populations, methodologies, exposure variables, and apparent overlap of outcome measures. Only the Friis et al's [22] study was included as it provided a better measurement of risk, stating standardized rate ratios (SRR).…”
Section: Included Studiesmentioning
confidence: 76%
“…Prescribing database studies Both Friis et al's studies [4,22] used drug-dispensing information from the Pharmaco-Epidemiological Prescription Database, North Jutland County, Denmark. Information on prescription medications dispensed since 1991 was linked to the Danish Cancer Registry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for OSCC therapy, only few conflicting data are available in literature on these drugs as chemo-preventive agents, since their real protective effect has not yet been entirely proven (4). Even less is known about the antineoplastic role of molecules which specifically address the COX-I isoform; in a large in vitro study on human colorectal cancer cells, Bottone et al (13) found that SC-560, a COX-I selective inhibitor was a more powerful apoptosis inductor than a COX-2 inhibitor on cancer cell lines; both act probably through gene expression modulation, though the underlying mechanisms are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, abnormal expression ofCOX-2 has been supposed to be related to the pathogenesis of human cancer by affecting cell proliferation and apoptosis, angiogenesis and immune surveillance against cancer (2). On the basis of such molecular findings, more recent in vitro and epidemiologic studies focus on the putative role of non-steroidal anti-inflammatory drugs (NSAIDs), and in particular COX-2 inhibitors, as more selective and side-effect free anti-neoplastic, or even chemopreventive, agents (3)(4)(5).…”
mentioning
confidence: 99%